Aquatic Resistome in Freshwater and Marine Environments: Interactions Between Commensal and Pathogenic in the Context of Aquaculture and One Health - Ana V. Mourão; Diana Fernandes; Telma de Sousa; Rita Calouro; Sónia Saraiva; Gilberto Igrejas; Patrícia Poeta (Microorganisms)
Aquatic resistomes are important reservoirs of antibiotic resistance genes (ARGs) and their precursors, which can proliferate and dissipate in pathogenic microorganisms that affect humans and animals, especially due to anthropogenic pressures such as the intensive use of antibiotics in aquaculture, often without effective regulation. This review addresses the mechanisms of horizontal gene transfer (HGT) in the dissemination of ARGs through mobile genetic elements (MGEs). In freshwater, genera such as Aeromonas, Pseudomonas and Microcystis stand out as vectors of ARGs. In the context of One Health, it is essential to implement sound public policies and strict regulations on the use of antibiotics in aquaculture, and the use of monitoring tools such as environmental DNA (eDNA) and metagenomics allows for the early detection of ARGs, contributing to the protection of human, animal and environmental health.